2011
DOI: 10.1007/s10751-011-0496-0
|View full text |Cite
|
Sign up to set email alerts
|

Vibration DOS of 57Fe and Zn doped rutile Sn(Sb) oxides

Abstract: Sn oxides co-doped with Zn, Sb and 57 Fe were prepared by sol-gel method, and especially the doping effect of non-magnetic Zn ions was studied. The bulk saturation magnetization is in accordance with the intensity of the magnetic component in Mössbauer spectra. The nuclear inelastic scattering (NIS) spectra of these compounds were measured in SPring 8. The vibration density of states (VDOS) of 57 Fe doped Sn(Sb) oxides showed that the softening peaks around 15-20 meV appeared by doping less than 10% Zn ions. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…FexSbySn1-x-yO2-δ [16] XRD peaks of Zn doped FexSbySn1-x-yO2-δ show only the rutile structure of SnO2 even if doped with Zn up to 7 %, whereas the spinel, Zn2SnO4, is additionally observed for more than 10 % Zn doped samples. XRD peaks of Zn2SnO4 are almost similar to those of spinel ZnFe2O4.…”
Section: Nonmagnetic Zn Dopedmentioning
confidence: 96%
See 2 more Smart Citations
“…FexSbySn1-x-yO2-δ [16] XRD peaks of Zn doped FexSbySn1-x-yO2-δ show only the rutile structure of SnO2 even if doped with Zn up to 7 %, whereas the spinel, Zn2SnO4, is additionally observed for more than 10 % Zn doped samples. XRD peaks of Zn2SnO4 are almost similar to those of spinel ZnFe2O4.…”
Section: Nonmagnetic Zn Dopedmentioning
confidence: 96%
“…A codoping technique that employs different d electron numbers becomes essential for the stabilization of ferromagnetism with the control of both saturation magnetization (Ms) and the coercive field (Hc) at RT. [20] Fe ION IMPLANTED SnO2 FILM [ [24] SnO2 film implanted with 5 × 10 16 Fe ions / cm 2 at 500 °C shows Kerr effect as shown in Figure 11. It is transparent Fe doped SnO2 film with high electric resistance.…”
Section: Sno2 Codoped With Two Transition Metal Ionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The doping effects of non magnetic Zn ions were also studied for Fe and Sb doped SnO 2 . It was found that the saturation magnetization increases with the addition of less than 10 % of non-magnetic Zn ions [13], and that Fe and Co [14,15] (Fe and Mn [16], or Fe and Ni [17]) co-doped SnO 2 gave rise to enhanced magnetization as compared with the single atom doped SnO 2 . In the case of diluted 57 Fe substituted at the Sn site in SnO 2 obtained by a sol-gel method, the experimental Mössbauer parameters were compared with ab initio calculations [18] to determine the local structure around iron in SnO 2 rutile structure.…”
Section: Introductionmentioning
confidence: 99%